The study and real-time implementation of attenuation correction for X-band dual-polarization weather radars - Liu, Yuxiang, author; Bringi, V. N., advisor; Chandrasekar, V., advisor (Colorado State University. Libraries, 2008)
Attenuation of electromagnetic radiation due to rain or other wet hydrometeors along the propagation path has been studied extensively in the radar meteorology community. Recently, use of short range dual-polarization X-band radar systems has gained momentum due to lower system cost compared with the much more expensive S-band systems. Advances in dual-polarization radar research have shown that the specific attenuation and differential attenuation between horizontal and vertical polarized waves caused by oblate, highly oriented raindrops can be estimated using the specific differential phase. This advance leads to correction of the measured reflectivity (Zh) and the differential reflectivity (Zdr) due to path attenuation. This thesis addresses via theory, simulations and data analyses the accuracy and optimal estimation of attenuation-correction procedures at X-band frequency. Real-time implementation of the correction algorithm was developed for the first generation of X-band dual-polarized Doppler radar network (Integration Project 1, IP1) operated by the NSF Center for Collaborate Adaptive Sensing of the Atmosphere (CASA). We evaluate the algorithm for correcting the Zh, and the Zdr for rain attenuation using simulations and X-band radar data under ideal and noisy situations. Our algorithm is able to adjust the parameters according to the changes in temperature, drop shapes, and a certain class of drop size distributions (DSD) with very fast convergence. The X-band radar data were obtained from the National Institute of Earth Science and Disaster Prevention (NIED), Japan, and from CASA IP1. The algorithm accurately corrects NIED's data when compared with ground truth calculated from in situ disdrometer-based DSD measurements for a Typhoon event. We have implemented, in real-time, the algorithm in all the CASA IP1 radar nodes. We also evaluate our preliminary method that separately estimates rain and wet ice attenuation using microphysical outputs from a previous supercell simulation using the CSU-RAMS (Regional Atmospheric Modeling System). The retrieved rain and wet ice specific attenuation fields were found to be in close correspondence to the 'true' fields calculated from the simulation. The concept to correct rain and wet ice attenuation separately can be also applied to the CASA IP1 network with additional constraint information possibly provided by the WSR-88D network.
Keywords: attenuation correction; CASA ip1; dual polarization; radar meteorology; radar remote sensing; weather radars; X-band weather radar; electrical engineering; atmospheric sciences; remote sensing